Pharmacological review of Vitex trifolia / Nur Afifah Mohd Shukri and Mizaton Hazizul Hasan - Mohd Shukri, Nur Afifah; Hasan, Mizaton Hazizul (Faculty of Pharmacy, 2021)
Vitex triflolia is one of the Vitex species where known as Lemuni. It is widely used traditionally to reduce pain, fever and minor ailments. Every part of the plant had its advantages; for example, the leaves part can relieve pain, treat fever and can help to improve memory. It has potent pharmacological activities such as antioxidant, antinociceptive, anti-inflammatory and anticancer. Other than that, every part of the plant has unique constituents with different biological activities. A few isolated and identified flavonoids in V. trifolia include casticin, persinogenin, artemetin, luteolin, penduletin, vitexicarpin and chrysisplenol. These flavonoids can inhibit the cell cycle involved in carcinogenesis and have been reported to have antiinflammatory properties. In putting together this review, PRISMA was adopted, which utilised two primary journal databases, Scopus and PubMed and a supporting database, Google Scholar. The search resulted in 17 journals for this review that covered the phytochemical constituents and pharmacological activities of V. trifolia. To conclude, this review provided insightful information on how the knowledge gap on V. trifolia can be exploited as possible treatments for COVID-19 as the extracts have shown potential anticancer, anti-inflammatory, antioxidant and other pharmacological properties due to the presence of the phytochemical constituents in the plant.